Single‐Atom Nanozyme Based on Nanoengineered Fe–N–C Catalyst with Superior Peroxidase‐Like Activity for Ultrasensitive Bioassays - Cheng, Nan; Li, Jin‐Cheng; Liu, Dong; Lin, Yuehe; Du, Dan (Small (Weinheim an der Bergstrasse, Germany), 2019)
Single‐atom catalysts are becoming a hot research topic owing to their unique characteristics of maximum specific activity and atomic utilization. Herein, a new single‐atom nanozyme (SAN) based on single Fe atoms anchored on N‐doped carbons supported on carbon nanotube (CNT/FeNC) is proposed. The CNT/FeNC with robust atomic Fe–Nx moieties is synthesised, showing superior peroxidase‐like activity. Furthermore, the CNT/FeNC is used as the signal element in a series of paper‐based bioassays for ultrasensitive detection of H2O2, glucose, and ascorbic acid. The SAN provides a new type of signal element for developing various biosensing techniques. A new single atom nanozyme (SAN), carbon nanotube supported single Fe atoms anchored on N‐doped carbon (CNT/FeNC), was developed for bioanalytical applications. The CNT/FeNC with robust atomic Fe–Nx moieties showed superior peroxidase‐like activity. A series of paper based bioassays were developed using SAN as the signal element.